GURU DAN PENGUATAN PENDIDIKAN KARAKTER - Aryni Ayu Widiyawati (Jantra., 2019)
This study aims to looks at character education which is a part of mental revolution which contains elements of education, character development, nationalism, and ethics. It also look at the teacher, who is the central figure in education and is always associated with the formation of character development. National education which is based on the Law on National Education (No. 20/ 2003) aims to develop the learners' potential and shape their character in order that they become individuals who are devotedly pious to God Almighty, healthy, proficient, knowledgeable, creative, independent, as well as to become responsible and democratic citizens. So that, eventually the learners can contribute to build a dignified civilization and nation. According to Lickona, character education is a deliberate attempt to help a person so as to understand, pay attention, and perform core ethical values, including values in national education. The data of this qualitative research were drawn from library research, observation, practice teaching, and in-depth interviews with related respondents. The results of this study indicate that the relation between teachers and character education refers to the functional structural theory of Robert K. Merton. His theory indicates that members and the body cannot be separated. Strategies to implement character education can be executed through: (I) providing a real model, (2) inculcating discipline, (3) establishing conducive atmosphere, (5) integrating and internalizing.